2014
DOI: 10.1186/ar4590
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of moxibustion treatment as adjunctive therapy in osteoarthritis of the knee: a randomized, double-blinded, placebo-controlled clinical trial

Abstract: IntroductionOur objective was to compare the effectiveness and safety of traditional Chinese moxibustion to that of sham moxibustion in patients with chronic knee osteoarthritis (KOA) pain.MethodsWe conducted a randomized placebo-controlled trial involving 110 patients with KOA who met the inclusion criteria. These patients randomly received either active moxibustion (n = 55) or sham moxibustion control (n = 55) at acupoints Dubi (ST 35), extra-point Neixiyan (EX-LE 4), and an Ashi (tender) point three times a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(85 citation statements)
references
References 29 publications
1
84
0
Order By: Relevance
“…Instead of stimulating acupuncture points using needles, moxibustion provides thermal stimulation of these points by burning the herb near them. Moxibustion has been practiced along with acupuncture in China for thousands of years to treat various disorders . Although empirically used for alleviating fatigue, to the best of our knowledge research concerning the effects of moxibustion for the treatment of CRF has only been reported in a few Chinese language articles to date.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead of stimulating acupuncture points using needles, moxibustion provides thermal stimulation of these points by burning the herb near them. Moxibustion has been practiced along with acupuncture in China for thousands of years to treat various disorders . Although empirically used for alleviating fatigue, to the best of our knowledge research concerning the effects of moxibustion for the treatment of CRF has only been reported in a few Chinese language articles to date.…”
Section: Introductionmentioning
confidence: 99%
“…Moxibustion has been practiced along with acupuncture in China for thousands of years to treat various disorders. 9,10 Although empirically used for alleviating fatigue, to the best of our knowledge research concerning the effects of moxibustion for the treatment of CRF has only been reported in a few Chinese language articles to date. Because of the high risk of bias and low reporting quality of these studies, it has been difficult to determine whether moxibustion is an effective and safe treatment for patients with CRF.…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise, 3 RCTs 20,21,23 noted region adverse reactions, for example, blisters, burn wounds, and skin flushing in local lesions. Two studies 21,23 reported systemic AEs; however, only 1 23 reported positive symptoms, that is, pruritus and fatigue.…”
Section: Resultsmentioning
confidence: 99%
“…The treatment acupoints and intervention period are based on some positive result studies and clinical experience in order to ensure their effectiveness [1113, 15]. …”
Section: Discussionmentioning
confidence: 99%